Arteriovenous malformation in the pancreatic head initially mimicking a hypervascular mass treated with duodenum-preserving pancreatic head resection: a case report - Takahiro Korai; Yasutoshi Kimura; Masafumi Imamura; Minoru Nagayama; Ayumi Kanazawa; Ryo Miura; Takeshi Murakami; Daisuke Kyuno; Hiroshi Yamaguchi; Kotomi Terai; Shintaro Sugita; Takayuki Nobuoka; et al. (Surgical Case Reports, 2020)
Abstract Background The mainstay treatment for arteriovenous malformation in the pancreatic head (Ph-AVM) is standard pancreatectomy, especially pancreaticoduodenectomy (PD), or interventional endovascular treatment. We report the first case of Ph-AVM treated with duodenum-preserving pancreatic head resection (DPPHR) performed to preserve the periampullary organs. Case presentation A 59-year-old man presenting with back pain underwent contrast-enhanced computed tomography followed by angiography of the anterior superior pancreaticoduodenal artery. He was diagnosed with Ph-AVM and indicated for DPPHR with preservation of the periampullary organs; Ph-AVM’s benign nature seldom requires lymph node dissection. During the operation, the right colon was mobilized and the omental bursa was released to expose the periampullary structures. The pancreas was transected just above the superior mesenteric vein. The inferior pancreaticoduodenal artery and papillary arteries branching from the posterior superior pancreaticoduodenal artery were carefully preserved to maintain the blood flow to the lower bile duct and papilla of Vater. The remnant pancreas was reconstructed with pancreaticogastrostomy using the modified Blumgart method. Pathological examination of the resected specimen revealed an irregular course of the arteries and veins concomitant with marked dilation throughout the pancreatic head. The patient was pathologically diagnosed with Ph-AVM. He developed hematemesis caused by a rupture of the pseudoaneurysm on postoperative day 20 and underwent coil embolization. A bilio-enteric fistula and stenosis of the common bile duct were found and treated by placement of an endoscopic biliary stent. At the 8-month follow-up, the Ph-AVM had not recurred. Conclusions Compared to PD, DPPHR confers the clinical benefit of preserving the periampullary organs, although further studies are needed to confirm this. Therefore, the choice of this procedure should be based on the surgical morbidities and long-term outcome of the patient.